Analisis Pendistribusian Surat Jalan Pada Facility, Workshop, Safety, Development Department PT United Tractors Tbk. - Jundira Jundira; Marsofiyati Marsofiyati; Amirul Adha, Maulana (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
This research aims to analyse the delivery order distribution process, identify the challenges encountered, and propose solutions for the conventional system at the Facility, Workshop, Safety, Development Department of PT United Tractors Tbk. The study employed a qualitative method using observation, interviews, and documentation as data collection techniques, with four informants selected through purposive sampling. The findings indicate that the delivery order distribution process follows established administrative procedures; however, several challenges remain, including discrepancies between delivery orders and Purchase Orders (PO), risks of data input errors due to manual recording, delays in document distribution and archiving, and the impact of personnel rotation. Therefore, the implementation of a more integrated and digital-based system is considered necessary to improve efficiency, data accuracy, and document management.